The Self-Efficacy Roles in Mediating Students’ Readiness to Become a Teacher (Universitas Negeri Semarang, 2022)
Universitas Negeri Semarang (UNNES) contributes to the availability of teachers. However, alumni of UNNES who work as teachers have decreased over the last two years. This study aims to analyze digital literacy, communication, creativity, and perception of the teaching profession to readiness to become a teacher and explores the influence of digital literacy, communication, creativity, and the teacher profession perception on readiness to become a teacher through self-efficacy. This research method is a quantitative study with a population of 350 Economic Education students, at the Faculty of Economics, UNNES batch 2018. The sample is 187 students. The sampling technique used in this study was proportional random sampling. Then, the descriptive test, path analysis, and Sobel test were the tests for the study. The findings show that simultaneously the four variables affect readiness to become a teacher by 68.9%. Then, digital literacy and communication positively and significantly affect readiness to become a teacher. However, creativity has a negative and insignificant effect on readiness to become a teacher; and teacher profession perception has a negative and significant impact on readiness to become a teacher. Further, indirectly digital literacy, mediated by self-efficacy, has a negative and insignificant effect on readiness to become a teacher. Communication, creativity, and teacher profession perception indirectly impact significantly the readiness to become a teacher. The students should join a seminar on the noble duties of teachers and teacher training to understand the teaching profession better.